(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we investigate the fuzzy aspects of split exact sequences, projective-injective and semi simple modules, theoretical results connecting them are supported by appropriate examples. Remarkable equivalence conditions are established to unveil the evenness of fuzzy projective-injective modules over semi simple rings. Also, towards the conclusion we have developed a procedure to compute injective dimension of a fuzzy module based on the possible length of injective resolution and illustrate its working by means of an example.